INVESTIGATING THE IMPLEMENTATION OF ENGLISH ZONE AT ENGLISH DORMITORY IN DARUSSALAM ISLAMIC BOARDING SCHOOL - Affan Tyas Aszhari; Sayid Ma'rifatulloh (JURNAL ILMIAH NUSANTARA, 2024)
The study investigates the implementation of the English Zone (EZ) in the English Dormitory at Darussalam Islamic Boarding School to enhance students' English-speaking skills. Given the global significance of English for communication, education, and professional success, particularly in non-native English-speaking countries like Indonesia, this research explores how an immersive language learning environment can facilitate language proficiency. The study focuses on the methods, strategies, challenges, and opportunities involved in creating an English-speaking zone, examining how structured rules, consistent practice, and supportive environments contribute to language development. The findings aim to provide insights into the effectiveness of the English Zone approach in promoting English language proficiency within a unique educational and cultural context, offering potential implications for similar language immersion programs.